Human-Induced CD49a+ NK Cells Promote Fetal Growth - Du, Xianghui; Zhu, Huaiping; Jiao, Defeng; Nian, Zhigang; Zhang, Jinghe; Zhou, Yonggang; Zheng, Xiaohu; Tong, Xianhong; Wei, Haiming; Fu, Binqing (Frontiers in Immunology, 2022)
CD49a+ natural killer (NK) cells play a critical role in promoting fetal development and maintaining immune tolerance at the maternal-fetal interface during the early stages of pregnancy. However, given their residency in human tissue, thorough studies and clinical applications are difficult to perform. It is still unclear as to how functional human CD49a+ NK cells can be induced to benefit pregnancy outcomes. In this study, we established three no-feeder cell induction systems to induce human CD49a+ NK cells from umbilical cord blood hematopoietic stem cells (HSCs), bone marrow HSCs, and peripheral blood NK cells in vitro. These induced NK cells (iNKs) from three cell induction systems display high levels of CD49a, CD9, CD39, CD151 expression, low levels of CD16 expression, and no obvious cytotoxic capability. They are phenotypically and functionally similar to decidual NK cells. Furthermore, these iNKs display a high expression of growth-promoting factors and proangiogenic factors and can promote fetal growth and improve uterine artery blood flow in a murine pregnancy model in vivo. This research demonstrates the ability of human-induced CD49a+ NK cells to promote fetal growth via three cell induction systems, which could eventually be used to treat patients experiencing adverse pregnancy outcomes.